Efectos de la aplicación de las Normas Internacionales de Información Financiera (NIIF) para Pequeñas y Medianas Empresas (PYMES) sección 13.19 deterioro de inventarios, en las empresas dedicadas a las ventas al por menor de artículos de ferretería ubicadas en el norte del Distrito Metropolitano de Quito, año 2020 - Ocejos Carapaz, Jonathan Esteban (2021)
Changes in technical regulations, quality standards of articles, expiration, technological or climatic changes in Ecuador, cause loss of value in inventories. We report the application of Section 13.19 Inventory Impairment of the International Financial Reporting Standards for SMEs in the sector in companies engaged in the retail sales of hardware items located in the North of the Metropolitan District of Quito, year 2020. We discuss the impact on worker participation and income tax caused, finding that they decrease by 0.15% and 0.11% respectively. The reduction is similar in both cases, the loss being of little significance.